PARTISIPASI MASYARAKAT DALAM PEMANFAATAN DANA PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN TERHADAP KEMAJUAN KESEJAHTERAAN MASYARAKAT (Studi di Desa Tetehosi I Kecamatan Gunungsitoli Idanoi) - Gea, Andriaman (PERSPEKTIF, 2016)
The research carried out in the village Tetehosi I sub district of Gunungsitoli Idanoi. While the issues raised with respect to this research is how the public participation in the utilization of the funds of the National Program for Community Empowerment in Rural Areas to the welfare of society. The method used in this research is descriptive qualitative approach. Results of research and discussion explains the different types of public participation in the National Program for Community Empowerment in Rural Areas in the village Tetehosi I sub district of Gunungsitoli Idanoi. With the participation of the community is able to create an effective development according to the needs of the community so that it has a significant impact on the progress of public welfare.